The Gendarmerie, (In-)Security and Popular Reaction in West Cameroon, Federal Republic of Cameroon 1961–1964 - Nkwi, Walter Gam; Kah, Henry Kam; Ndeh, Martin Sango (Modern Africa: Politics, History and Society, 2016)
The presence and activities of the Gendarmerie is as old as French influence in Africa. Since the re-birth of multi-party politics during the 1990s in Cameroon, the military crackdown in erstwhile West Cameroon rekindled old memories of Gendarmerie brutality and popular reaction. As a paramilitary force, it was charged with the provision of security but instead instilled fear and insecurity in the West Cameroon state. This article examines the activities of the Gendarmerie and pays close attention to the tradition and origin of this paramilitary force in West Cameroon. What circumstances led to the introduction of the Gendarmerie in West Cameroon? What was the strength of the West Cameroon security forces before the introduction of the Gendarmerie in 1961? In providing answers to these questions we consulted documents from the National Archives Buea in Cameroon and secondary sources from libraries. These sources reveal that the Gendarmerie force was abhorred by many West Cameroonians. This was because of the brutality of Gendarmes on the civilian population, police and custom officers. The paper also contends that, although the Gendarmerie corps was out to ensure peace and security, it became more or less an insecure force to property and the lives of the West Cameroonian population, as well as to the police and custom officials in West Cameroon.